The Homeschooling Head Performance: How The Role of Transformational Leadership, Motivation, and Self-Efficacy? - Haq, Saiful; Asbari, Masduki; Sukriyah; Novitasari, Dewiana; Abadiyah, Siti (International Journal of Social and Management Studies, 2022)
This study aims to analyze the relationship of transformational leadership, motivation, and self-efficacy to the Head of homeschooling performance. This research method is quantitative with data processing tools using SPSS software. Data were obtained through the distribution of online questionnaires to 212 homeschooling teachers in Tangerang who were selected using the simple random sampling method. Based on data analysis, it can be concluded that transformational leadership has a positive effect on the head of homeschooling performance, motivation has a positive effect on the head of homeschooling performance, self-efficacy has a positive effect on the head of homeschooling performance and transformational leadership, motivation, and self-efficacy simultaneously have a positive and significant effect on the head of homeschooling performance.